Mediasi City Branding pada Pengaruh Kesadaran Merek, Asosiasi Merek, dan Kesan Kualitas Terhadap Keputusan Memilih Perguruan Tinggi Negeri di Surabaya - Ria Astuti Andrayani; Sri Setyo Iriani (Jurnal Manajemen dan Bisnis Indonesia, 2014)
Education is a major concern of government in enhancing and improving the quality of human resources. Indonesia have stratified formal education which higher education contains of state university and private university. Surabaya is a city in Indonesia which has the largest public universities. There are four universities, there are universitas airlangga (UA), universitas negeri Surabaya (Unesa), institut teknologi sepuluh nopember (ITS), and IAIN sunan ampel. This study aims to test and analyze whether brand awareness, brand association, and perceived quality affect decision to choose state universities in Surabaya. This type of this research is quantitative, using multistage sampling with 377 respondents. Statistical analysis that used is the approach of mutiple linear regression which tested to every object. The results of this study showed that brand awareness and perceived quality has a positive influence on the decision to choose state universities in Surabaya. there are differences in the effect of brand association that the UA and Unesa positive influence while at IAIN Sunan Ampel, ITS and negative effect. Those influences has different athmosphere by respondent of Surabaya’s city branding. There’s not all of the respondent to consider city branding of Surabaya when they choose to study at Surabaya. Keywords: brand awareness, brand association, perceived quality, decision to choose, state university